Appetite Regulation of TLR4-Induced Inflammatory Signaling - Li, Yongxiang; Jiang, Qingyan; Wang, Lina (Frontiers in Endocrinology, 2021)
Appetite is the basis for obtaining food and maintaining normal metabolism. Toll-like receptor 4 (TLR4) is an important receptor expressed in the brain that induces inflammatory signaling after activation. Inflammation is considered to affect the homeostatic and non-homeostatic systems of appetite, which are dominated by hypothalamic and mesolimbic dopamine signaling. Although the pathological features of many types of inflammation are known, their physiological functions in appetite are largely unknown. This review mainly addresses several key issues, including the structures of the homeostatic and non-homeostatic systems. In addition, the mechanism by which TLR4-induced inflammatory signaling contributes to these two systems to regulate appetite is also discussed. This review will provide potential opportunities to develop new therapeutic interventions that control appetite under inflammatory conditions.